Pagan family values: childhood and the religious imagination in contemporary American paganism - Kermani, S. Zohreh (The new and alternative religions series, 2013)
""An intriguing, important, and often entertaining look at an under-studied aspect of new religions. Highly recommended."" -Douglas E. Cowan, author of Cyberhenge: Modern Pagans on the Internet For most of its history, contemporary Paganism has been a religion of converts. Yet as it enters its fifth decade, it is incorporating growing numbers of second-generation Pagans for whom Paganism is a family tradition, not a religious worldview arrived at via a spiritual quest. In Pagan Family Values , S. Zohreh Kermaniexplores the ways in which North American Pagan families pass on their beliefs to